Pengaruh Temperatur Tuang, Temperatur Cetakan, dan Tekanan Pada Pengecoran Bertekanan (High Pressure Die Casting/HPDC) Terhadap Kekerasan dan Struktur Mikro Aluminium Paduan Silikon (Al-Si 7,79 %) - Sulis Drihandono; Eko Budiyanto (TURBO [Tulisan Riset Berbasis Online], 2016)
The purposes of this research are to investigate the effect of mold temperature, melting temperatur, and pressure on micro structure and hardness. The alloy used is Al-Si 7,79% using the High Pressure Die Casting (HPDC) method.HPDC is a casting method with injection the metal liquid to the cavity mold with specific speed and pressure. This research used 3 variations, they are pressure (50 bar, 75 bar, and 100 bar), melt temperature (700°C, 750 °C, and 800°C), and molding temperature (250°C, 300°C, and 350°C).Observations were made on the microstructure of the alloys show that Al-Si 7.79% showed some similar changed which is the tendency of the silicon phase will become thick silicon chip and the primary is likely to change even greater. This condition is caused by an increase in time solidification with increasing melt temperature and the mold temperature. The hardness in general will increase with increasing temperature and pressure. The highest hardness is 79,94 BHN at mold temperature of 250 °C, melt temperature of 750 ° C and pressure of 75 bar.